2016
DOI: 10.1007/s13205-015-0361-y
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of soil bacteria in some areas of Midnapore coastal belt, West Bengal, India

Abstract: In this present study the population dynamics of the soil bacteria of some coastal villages, namely Padima, Jatimati, Chanpabani, Palsandapur, Bhagibaharampur, Duttapur, Gangadharpur, Gobindabasan, Somaibasan of Digha, West Bengal, India, was determined. In these villages the aerobic heterotrophic, Gram-negative, spore-forming, starch-hydrolyzing, Pseudomonas, nitrate-reducing, denitrifying, asymbiotic N2 fixing, nitrifying, phosphate-solubilizing bacterial populations ranged from 1.22 to 2.67 × 106, 0.09–1.63… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The reason for such variation may be attributed to the differences in the microhabitats of the areas studied which, in a way, may be correlated to the physico-chemical parameters of the soil from these sacred patches as well. These results again support the views of earlier workers like Bever (1994), Mandic-Mulec and James (2011), Azmi and Chatterjee (2016), Rashid et al (2016) and Wang et al (2020). The correlation among the bacterial groups depending on their relative density was highlighted by clustering analysis (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The reason for such variation may be attributed to the differences in the microhabitats of the areas studied which, in a way, may be correlated to the physico-chemical parameters of the soil from these sacred patches as well. These results again support the views of earlier workers like Bever (1994), Mandic-Mulec and James (2011), Azmi and Chatterjee (2016), Rashid et al (2016) and Wang et al (2020). The correlation among the bacterial groups depending on their relative density was highlighted by clustering analysis (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…The study on the nutrient status of soil samples from some sacred patches of Maharashtra by Sathe et al (2018) is also worth mentioning. However, similar studies on soil microbial diversity from different areas, other than sacred patches, include those by Das et al (2013), Radhakrishnan and Varadharajan (2016), Azmi and Chatterjee (2016), Sharma et al (2019); The viable plate count method was applied to study the bacterial diversity of the soil samples in the current investigation. The aerobic heterotrophic bacterial population from the sacred patches were quite high which indicates high composition of organic matters in the soil.…”
Section: Discussionmentioning
confidence: 91%
“…Gömöryová et al [35] studied the distribution of functional groups of microbes via BIOLOG analysis and found organic carbon as an important functional group influencing microbial diversity in soil. Physicochemical properties of soils also influenced the soil microbial diversity pattern [9,10]. The two-way ANOVA study revealed that in Digha coastal belt the Bacillus diversity varied significantly both in spatial and in temporal aspects which may be due to the variation in the microhabitat present in these areas in different seasons.…”
Section: Discussionmentioning
confidence: 99%
“…After incubation, the colonies grown in those media were observed thoroughly for screening of the Bacillus colonies and a portion of each colony was observed under microscope to observe the rod shaped vegetative cells. The Bacillus colonies were then enumerated and total colony forming unit (cfu)/g of dry soil was calculated [9,10]. slants and stored at 4 ∘ C for further characterization.…”
Section: Culture and Enumeration Of The Bacillus Colonies Frommentioning
confidence: 99%
“…The nitrate agar medium and spirit blue agar medium with TWEEN 20 were used to determine NRed and FHydro groups respectively. These groups of bacterial populations were determined after 1-3 days of incubation [29,30,31,32] . PHydro group of bacteria was determined by the presence of a halo zone around the colonies by flooding with HgCl 2 on nutrient agar medium with 2% gelatine.…”
Section: Rhizosphere Bacteria Analysismentioning
confidence: 99%